Modelling percolation and fractal structure in aerogels - Araújo, Adérito (2014)
Active Space Technologies is interested in having a better understanding of the processes by which aerogels are produced so that, in particular, it can improve its control over the resulting aerogel properties. The study group was asked to concentrate on two particular characteristics of aerogels, namely, percolation (which models to use) and fractal dimension (how to estimate it from available images).